Quality of life improvement in patients with hard-to-heal leg wounds treated with Prontosan wound irrigation solution and wound gel. (2nd October 2021) - Oropallo, Alisha; Snyder, Robert J; Karpf, Angela; Valencia, Diana; Curtin, Christopher R; Cetnarowski, Wes
Abstract : Objective: This study evaluated the impact of four weeks of treatment with Prontosan Wound Irrigation Solution and Prontosan Wound Gel (B. Braun Medical Inc., US) on adults with hard-to-heal leg wounds. Overall change (weeks 1–5) in the Global Quality of Life scale (GQOL), changes in body, psyche and everyday life (EDL) quality of life (QoL) subscores, and changes in wound appearance and size after treatment were assessed. Method: In this prospective, open-label, single-arm, five-centre study, non-hospitalised patients with no more than two wounds below the knee were recruited into the study; wounds were ≥5cm 2 and ≤50cm 2 and present for ≥4 weeks. The investigator or a designee applied the wound solution and gel to the wounds at clinic visits, and patients/caregivers applied the wound solution and gel at home. Wound-QoL questionnaires were completed at the initial screening and at each week of treatment. Wound size and photographs were obtained at pre- and post-treatment during clinic visits. Results: A total of 43 patients were enrolled in the study. Mean GQOL scores decreased by 1.11 (46.1%). Body, psyche and EDL decreased by 1.17 (60.0%), 1.26 (41.8%) and 1.00 (42.2%), respectively. Wounds also showed improvement in odour, appearance and size. Adverse events were mild in intensity and transient in nature. Conclusion: This study demonstrated marked improvement in the QoL of patients with hard-to-heal leg wounds below the knee during four weeks of treatment with the wound solution and gel. Wounds also showed improvement in odour, appearance and size, and the treatment solution and gel were well tolerated. Declaration of interest: B. Braun Medical Inc. funded the research and preparation of this article. AK, DV, CRC and WC are employees of B. Braun Medical Inc. AO and RS declare no conflict of interest.